Deloc: a delegation-based privacy-preserving mechanism for location-based services. (25th November 2020) - Sahnoune, Zakaria; Aïmeur, Esma
Location-based services (LBSs) are everywhere; we found them in several fields such as healthcare, entertainment, transportation, and many other daily activities. Besides, along with their presence in almost every daily task, their usefulness cannot be ignored. Moreover, with smartphone ownership growth, getting one's location became easier, and the privacy-related issues became almost inescapable. Hence, more severe solutions are strongly required to handle privacy issues and to keep LBS utility. We present in this paper Deloc, a novel location privacy protection mechanism founded on the idea of preserving location privacy without altering geographical coordinates. We introduce a new set of concepts and definitions that allow us to meet high privacy guarantees and data accuracy by delegating one's request to other LBS users. Similarly, we investigate the privacy issues related to LBSs along with state-of-art protection approaches and techniques. We evaluate Deloc on both synthetic and real-world data in a finely simulated environment with tunable parameters, and demonstrate its efficiency and usefulness in today's LBS applications, along with its higher privacy guarantees in respect to differential privacy standards.